Nekrolog over Poul Borum - Jensen, Jørgen I. (Grundtvig-Studier, 1997)
Poul Borum 1931-1996 By Jørgen I. Jensen Jørgen I. Jensen has written an obituary of the Danish literary critic and poet Poul Borum, whose book The Poet Grundtvig (Digteren Grundtvig) stands out as an essential contribution to the understanding of Grundtvig with implications far beyond the borders of literary criticism.